Simplify the expression first and then substitute 2 for x. 9x+6+4x+5=?

8 Answers

Relevance
  • zipper
    Lv 7
    2 months ago

    9x=6=4x=5+?   9x+11=4x+?  9x2+11+4x2=37

  • 2 months ago

    9x+6+4x+5=

    13x + 11  (Simplified) 

    13(2) + 11 = 

    26 + 11 = 37  (2 substituted)

  • 2 months ago

    9x+6+4x+5

    1. Group like terms

    (9x+4x) + (6+5)13x+11

    2. Substitute 2 for x => 13*2+11

    3. Work out

    26+11=37

  • 2 months ago

    you do 9x + 4x which is 13x, because 9+4=13

    Then you add the 6 and 5 together so, 6+5=11

    finally add the two terms together so 13x+11

    If you want to work out when x=2 you multiply

    13 by 2 because of the 3x so 13*2=26

    then add the 26 to the 11 so, 26+11

    = 37 this is your answer

  • What do you think of the answers? You can sign in to give your opinion on the answer.
  • 2 months ago

    9x + 6 + 4x + 5 

    = 13x + 11

    = 37 (for x = 2)

  • 2 months ago

    9x + 6 + 4x + 5

    1) Simplify by combining like terms

    After you combine 9x with 4x, and the 6 with the 5, you get this:

    13x + 11 <-- simplified

    2) Sub in 2 in the place of x

    13(2) + 11

    3) Evaluate the expression for "x equals 2"

    26 + 11

    37 <-- evaluated for "x equals 2"

  • 2 months ago

    9x+6+4x+5 = 9x+4x+11 = x(9+4)+11 = x(13)+11 = 13x+11

    ?=13(2)+11=37

    thus the unknown variable = 37

  • ?
    Lv 7
    2 months ago

    9x+4x+6+5

    =13x+11

    =13x2+11

    =26+11

    =37

Still have questions? Get answers by asking now.